Comparative Study of the Cure and Mechanical Properties of Natural Rubber/Expandable Graphite Vulcanizate Filled with Nano and Precipitated Calcium Carbonate - S. Fernandez, Sheela; Kunchandy, Sam (Asian Journal of Chemistry, 2013)
A comparative study was performed of nano-CaCO3 and precipitated calcium carbonate as fillers in natural rubber/expandable graphite vulcanizates. A number of vulcanizates with different loadings of the fillers were prepared using a two-roll mill and moulded on a compression moulding machine. Effects of filler dosage on the cure and mechanical properties of the flame retardant natural rubber/expandable graphite vulcanizates were examined. Because of the reduction in the size of the nano CaCO3, drastic improvement in the mechanical properties were found in comparison with precipitated calcium carbonate filled natural rubber/expandable graphite composites. Furthermore, cure properties showed that nano CaCO3 filled natural rubber vulcanizates exhibited lower cure time than the precipitated calcium carbonate filled natural rubber/expandable graphite vulcanizates. The values of the swelling ratio of the nano CaCO3 filled vulcanizates decreased remarkably and are lower than the precipitated calcium carbonate filled natural rubber vulcanizates. There is an indication that that the optimum level of incorporation of nano CaCO3 is 6 phr.